Marketing Management: Education Business Strategi Marketing Universitas Swasta Studi Kasus Universitas Kristen Satya Wacana - Anggreani Sarah Yonaha Saroinsong (Syntax Corporation Indonesia, 2024)
This research aims to provide theoretical benefits by developing science and theory regarding SWOT analysis and the promotion mix of Satya Wacana Christian University (UKSW), as well as adding literature for further research. The type of research that will be used by the researcher is a qualitative approach and qualitative research. The researcher uses a qualitative approach with a type of descriptive research. The unit of analysis in this study is SWOT